Measures of blood pressure and cognition in dialysis patients. Issue 1 (20th June 2012) - Giang, Lena M.; Tighiouart, Hocine; Lou, Kristina V.; Agganis, Brian; Drew, David A.; Shaffi, Kamran; Scott, Tammy; Weiner, Daniel E.; Sarnak, Mark J.
Abstract There are few reports on the relationship of blood pressure with cognitive function in maintenance dialysis patients. The Cognition and Dialysis Study is an ongoing investigation of cognitive function and its risk factors in six Boston area hemodialysis units. In this analysis, we evaluated the relationship between different domains of cognitive function with systolic and diastolic blood pressure, pulse pressure, and intradialytic changes in systolic blood pressure, using univariate and multivariable linear regression models adjusted for age, sex, race, education, and primary cause of end‐stage renal disease. Among 314 participants, mean age was 63 years; 47% were female, 22% were African American, and 48% had diabetes. The mean (SD) of systolic blood pressure, diastolic blood pressure, pulse pressure, and intradialytic change in systolic blood pressure were 141 (21), 73 (12), 68 (15), and −10 (24) mmHg, respectively. In univariate analyses, the performance on cognitive tests primarily assessing executive function and processing speeds was worse among participants with lower diastolic blood pressure and higher pulse pressure. These relationships were not statistically significant, however, in multivariable analyses. There was no association between cognitive function and systolic blood pressure or intradialytic change in systolic blood pressure in either univariate or multivariable analyses. We found no association between different measures of blood pressure and cognitive function in cross‐sectional analysis. Longitudinal studies are needed to confirm these results.